Which Factors do Parents of Offspring with Intellectual Disability Experience as Promoting Inclusive Education for their Children? - Bachke, Carl Chr. (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
The background of this research is that few studies on inclusive education internationally, use parents as informants. Even fewer emphasize their positive experiences only. From the Norwegian support organisation for people with intellectual disability 14 parent-members were selected and qualitatively interviewed about their positive experiences with inclusive education for their offspring. By means of a discourse analytic approach their statements about constructive factors were benchmarked with twelve formerly identified literature-based factors in order to investigate which of twelve factors were validated by parental experiences, and to detect possible new factors. The general research question illuminated is which factors do parents of offspring with intellectual disability experience as promoting inclusive education for their children? The results are linked to the following four sub-questions: (1) which of the factors, disclosed in current literature, is frequently mentioned by the informants; (2) which new factors are disclosed; (3) which factor is so frequently mentioned that it is considered substantial; and (4) which factors might be combined, and possibly renamed? The results show that the informants contributed all in all with 18 factors. In the discussions it was argued that five factors were interpreted as new, four factors proved to be substantial, that a fifth factor almost gained equal status, while three more factors were considered vital. These eight factors represented the main answer to the research question, and were summarised in metaphoric model, baptized” the school-house of inclusive education”.